2022
DOI: 10.3389/fonc.2022.926296
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of N7-Methylguanosine Modification of Messenger RNA in Drug-Resistant Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is an aggressive hematological tumor caused by the malignant transformation of myeloid progenitor cells. Although intensive chemotherapy leads to an initial therapeutic response, relapse due to drug resistance remains a significant challenge. In recent years, accumulating evidence has suggested that post-transcriptional methylation modifications are strongly associated with tumorigenesis. However, the mRNA profile of m7G modification in AML and its role in drug-resistant AML are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Chemotherapy remains the main option for most AML patients. Recent studies have shown that m 7 G-related regulators are highly expressed in AML and can affect the proliferation of leukemic stem cells; also, m 7 G mRNA modification levels are significantly elevated in drug-resistant AML cell lines ( 17 , 18 ). However, there is still a lack of studies of specific mechanisms by which m 7 G affects AML development and treatment, and its relevance to AML prognosis still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy remains the main option for most AML patients. Recent studies have shown that m 7 G-related regulators are highly expressed in AML and can affect the proliferation of leukemic stem cells; also, m 7 G mRNA modification levels are significantly elevated in drug-resistant AML cell lines ( 17 , 18 ). However, there is still a lack of studies of specific mechanisms by which m 7 G affects AML development and treatment, and its relevance to AML prognosis still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…METTL1 and WDR4 are significantly overexpressed in AML samples and knockdown of METTL1 effectively inhibits the growth of leukemic stem cells ( 17 ). A recent transcriptome-wide study of differential m 7 G methylationome profiling showed that drug-resistant AML cells had significantly different levels of m 7 G mRNA modification from AML cells and were significantly enriched in drug resistance-associated mRNA ( 18 ). These findings suggest that m 7 G methylation modifications have potential predictive value for the prognosis of AML.…”
Section: Introductionmentioning
confidence: 99%
“…p53, BRCA1) 4 . Additionally, a recent transcriptome‐wide profiling study of internal m 7 G revealed a significantly lower internal m 7 G level on ABC transporter‐encoded transcripts (key players in multidrug resistance) in drug‐resistant acute myeloid leukaemia (AML) cells than in regular AML cells 5 . Therefore, targeting the dysregulated m 6 A/m 7 G machinery appears to be a promising strategy to overcome cancer chemoresistance (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…N7-methylguanosine (m 7 G) modi cation occurred at tRNA G46, mRNA 5' cap and rRNAs [22]. Recent studies also report that a considerable m 7 G modi cation occurred at internal mRNAs [23][24][25]. The m 7 G modi cation is catalyzed by a highly conserved methyltransferase complex -methyltransferase like 1 (METTL1) and WD repeat domain 4 (WDR4) in mammalian [26,27].…”
Section: Introductionmentioning
confidence: 99%